The effect of herbicide formulations and soybean genotype on the relationship between beneficial organisms and root pathogens - Allemann, Anette (University of the Free State, 2019)
There has been considerable speculation in the media that glyphosate has a negative impact on symbiotic micro-organisms, particularly in the case of genetically modified soybeans. This speculation coincides with the assumption that the presence of the RR® gene is detrimental to ability of rhizobacteria to infect genetically modified soybeans and stimulate nodule formation. Also postulated was that the presence of the gene weakens the resistance of the crop to soil borne pathogens. This thesis tested the hypothesis that glyphosate has an effect on soybean plants and its symbiotic rhizobacteria and that genetic modification of the plant is detrimental to successful rhizobium colonisation and disease resistance. A definite weakness in previous studies is that only one glyphosate formulation was used and that according to the literature no studies have used isolines of soybeans to compare interactions. In trials utilising a strain of Bradyrhizobium japonicum recommended by the Agricultural Research Council of South Africa, (WB74), and direct exposure of rhizobacteria to different glyphosate formulations showed no significant reduction of number of colonies. Neither did any of the treatments inhibit the ability of treated bacteria to infect both soybean isolines’ plant roots and stimulate the formation of active nodules. When exposing the RR® soybeans to different glyphosate formulations, the only negative effects on the different plant parts were found in cases where fertilisation with NH4NO3 was used instead of inoculation with the rhizobacteria. This result emphasised the importance of successful inoculation with the correct rhizobacterium. When the RR® soybeans were exposed to different glyphosate formulations in the presence of three soil pathogens, it was only plants treated with NH4NO3 that showed detrimental effects. Since these trials were not taken to harvest, it is not possible to speculate on ultimate yield in these cases. To investigate the presence of the RR® gene and its effect on soybean growth, both lines were treated in the exact same manner and cultivated under the same conditions. No significant differences were observed in any plant parameters, especially the mass of active nodules formed. When the growth parameters of the soybean lines were compared after exposure to soil pathogens, no significant differences in infection were observed. The presence of the RR® gene therefore does not appear to increase the susceptibility of soybean to soil borne pathogens.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2019
Keywords: Herbicide; Glyphosate; Legumes; Rhizobia; Arbuscular mycorrhiza; Roundup® Ready gene; Soybean; Pathogens